Language Preferences, Attitudes and Practices: A Pakistani Higher Education Perspective - Dr. Nagina Kanwal (corresponding author); Dr. Heena Saifullah Amjad; Dr. Sohail Younas (Al-Qanṭara, 2022)
Pakistan is a multilingual country where the language trend has a significant impact on language policies implemented at the higher educational level. It has always been difficult in Pakistan to decide which language will be used as the primary language of instruction at the higher educational level as there is always a choice between Urdu, English, and regional languages. The research aims to identify the language attitudes of teaching staff toward multilingualism at the higher educational levels, while considering the practices of the institution members, including the teaching staff and management, in order to comprehend the effects of a language policy on a particular academic community. Hence this research probes into the variables that the teachers associate with the notion of languages and multilingualism in higher education. The research conducts a survey in three undergraduate degree awarding institutes. The survey takes a sample of 50 teachers and their responses to the questionnaire in addition to 9 members of the administration who are interviewed so as to find out their views regarding language policy and its implementation on the premises of their institutes. The research study helps in revealing the ideologies of the members involved in the process of higher education, and also the importance for teachers and administration to be aware of the outcomes of implementing Urdu, English, or both at the undergraduate level in Pakistan.